Ventricular Septal Rupture After Blunt Chest Trauma in an Infant: A Case Report and Mini-Review - Zhu, Xu; Ji, Xiaojuan; Wu, Chun; Ho, Harvey; Jiang, Kunfeng; Wang, Yanqin; Bai, Ke (Frontiers in Pediatrics, 2020)
A ventricular septal rupture (VSR) due to blunt chest trauma (BCT) is rare in pediatrics. Children with traumatic VSR had an increased mortality risk. Traumatic VSR should be considered in infants with acute congestive cardiac failure following blunt trauma to the chest. Echocardiography is the method of choice for diagnosis and guiding the management of VSR. In this paper, we report a case of VSR caused by BCT in a 1-year and 9-month-old infant, who was diagnosed by emergency bedside echocardiography. We also provide a mini-review of literatures on BCT-induced VSR in children.